2010
DOI: 10.1302/0301-620x.92b1.22137
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomised controlled study comparing subacromial injection of tenoxicam or methylprednisolone in patients with subacromial impingement

Abstract: We have carried out a prospective double-blind randomised controlled trial to compare the efficacy of a single subacromial injection of the non-steroidal anti-inflammatory drug, tenoxicam, with a single injection of methylprednisolone in patients with subacromial impingement. A total of 58 patients were randomly allocated into two groups. Group A received 40 mg of methylprednisolone and group B 20 mg of tenoxicam as a subacromial injection along with lignocaine. The Constant-Murley shoulder score was used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 31 publications
1
44
2
3
Order By: Relevance
“…A prospective, randomized, controlled study comparing subacromial corticosteroid injections with subacromial tenoxicam injections demonstrated a significant improvement in shoulder functions with corticosteroids at 6 wks. 22 Contrary to all of the studies mentioned here, Ekeberg et al 5 reported no important differences in short-term outcomes between local corticosteroid injections and systemic corticosteroid injections in rotator-cuff disease. Vecchio et al 23 reported that the combination of subacromial corticosteroids and local anesthetics was not superior to local anesthetics used alone.…”
Section: Us-guided Injections In Shoulder Paincontrasting
confidence: 59%
“…A prospective, randomized, controlled study comparing subacromial corticosteroid injections with subacromial tenoxicam injections demonstrated a significant improvement in shoulder functions with corticosteroids at 6 wks. 22 Contrary to all of the studies mentioned here, Ekeberg et al 5 reported no important differences in short-term outcomes between local corticosteroid injections and systemic corticosteroid injections in rotator-cuff disease. Vecchio et al 23 reported that the combination of subacromial corticosteroids and local anesthetics was not superior to local anesthetics used alone.…”
Section: Us-guided Injections In Shoulder Paincontrasting
confidence: 59%
“…33 The final injection study, which compared patient treatment with subacromial steroid injection with a subacromial tenoxicam injection, demonstrated a statistically significant improvement in the steroid-treated patient group as measured by using the Constant Murley Shoulder Score. 34 Three studies compared use of ESWT with other treatments. High-level and low-level ESWT were compared.…”
Section: Rotator Cuff Tendinosismentioning
confidence: 99%
“…Karthikeyan et al [12] compared the efficacy of a single subacromial injection of tenoxicam, with a single injection of methylprednisolone in patients with impingement syndrome. Although tenoxicam injection exerted positive effects, they found significantly greater improvements in the methylprednisolone group.…”
Section: Discussionmentioning
confidence: 99%